UPAYA MENINGKATKAN KOLABORASI MELALUI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA PESERTA DIDIK KELAS 2 SDN LIDAH KULON I/464 SURABAYA - Nurul Fatwiyah, Rofika; Sukartiningsih, wahyu; Asari, ini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem-based learning (PBL) learning model is a learning approach that really supports collaboration between students. Collaboration can improve social skills, the ability to work together, responsibility, and the ability to apply the knowledge and skills learned in a deeper and more meaningful context. The aim of this research is to describe the application of the problem-based learning (PBL) model in increasing collaboration between class II students at SDN Lidah Kulon I/464 Surabaya. This research uses a type of classroom action research (PTK) carried out in two cycles. This research went through four stages, namely planning, implementation, observation, and reflection. Data collection techniques include observation and documentation. The results obtained prove a significant increase in Cycle I and Cycle II. In cycle I, the observation results reached a percentage of 69%, while the increase in cycle II reached a percentage of 85%. Increasing student collaboration includes three aspects that are assessed, namely cooperation, social skills, and responsibility. Based on this, the application of problem-based learning (PBL) in Pancasila education can increase the collaboration of class II students at SDN Lidah Kulon I/464 Surabaya.